2018
DOI: 10.9734/indj/2018/45409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Abusive Behaviours in Upper Egyptian Adolescents: Violence, Sexual Abuse Victimisation, and Substance Abuse among Blood Group Types Subsets

Abstract: Deviant behaviours, namely physical violence, sexual abuse; illicit drug use are globally spreading risks. They tend to be socially concealed, rendering evaluating their impact upon population subsets difficult. Aim: Analyse trends and correlates of violence, sexual abuse, and substance abuse victimisation among adolescents in Upper Egypt. Methods: Youth aged 15-21 were randomly selected and cross-sectioned; and a validated questionnaire was used to achieve study aim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In general, men were significantly more likely than women to report direct and witnessed exposure to sociopolitical violence. These findings are consistent with literature reporting men’s higher level of exposure to community and political violence (Afifi et al, 2018; Ribeiro et al, 2009). Women, however, reported higher rates of both experiencing and learning about looting of homes and businesses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, men were significantly more likely than women to report direct and witnessed exposure to sociopolitical violence. These findings are consistent with literature reporting men’s higher level of exposure to community and political violence (Afifi et al, 2018; Ribeiro et al, 2009). Women, however, reported higher rates of both experiencing and learning about looting of homes and businesses.…”
Section: Discussionsupporting
confidence: 92%
“…In examining trauma and trauma-related distress, it is crucial to recognize potential variation across sociodemographic groups. Research on low-to-middle-income country contexts and Egypt specifically, has suggested that women may be more likely to experience interpersonal forms of violence, while men have higher rates of community violence exposure (Afifi et al, 2018; Ribeiro et al, 2009). To date, few studies in Egypt have examined gender differences in trauma exposure; one inpatient study by Eldabah et al (2016) suggested women were more likely than men to report depression, posttraumatic stress severity, and sexual violence exposure.…”
mentioning
confidence: 99%